Propuesta de optimización del proceso de recibo de combustible por líneas submarinas en el terminal pozos colorados de la ciudad de Santa Marta. (2020)
The research carried out had the general objective of proposing an optimization plan for the FUEL RECEIPT PROCESS by Submarine Lines at the Pozos Colorados Terminal in the city of Santa Marta to reduce Operating Costs. To achieve this, different sources of information from authors and institutions specialized in the study topic were consulted, such as Ford (2015), Cardeñosa (2013), ICONTEC (2015), UN (2018), TERPEL, SA (2015), among others. . Methodologically, the study was descriptive, framed as a cross-sectional or transectional experimental design, and was oriented by the hypothetical-deductive method, generating the research hypothesis. The population consisted of fourteen (14) operating subjects of different levels from the Pozos Colorados Terminal. To collect the information, the survey was used as a technique and a Likert scale questionnaire, consisting of thirty-nine (39) questions and five (5) response options, validated by three experts; the reliability of the same was determined by means of the Alpha coefficient of Crombach at 0.846 to place it in a very high magnitude range. The collected data were statistically analyzed with the IBM-SPSS package and the EXCEL spreadsheet were tabulated in absolute and relative frequency tables, generating the mean and standard deviation to measure the behavior of the variable. The percentage distribution of the responses obtained was summarized in a pie chart. The results of the study determined that there is compliance with the proposed objectives, concluding in the favorable trend for the feasibility of proposing an optimization plan for the FUEL RECEIPT PROCESS by Submarine Lines at the Pozos Colorados Terminal in the city of Santa Marta for the reduction of operating costs